TRADITIONAL CHINESE MEDICINE TONGXINLUO PROTECTS MICROVASCULAR FROM ARTERIOLE SPASM INDUCED BY NOREPINEPHRINE IN RATS MESENTERY - Zhang, Jun xiu; Li, Shao dan; Liu, Yi; Yang, Ming hui (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Arteriole spasm (AS) served as a common pathogenesis of many diseases. Tongxinluo (TXL), a traditional Chineseformula, has been proved to benefit patients with diseases associated with AS. However, the effect of TXL on AS has not beenelucidated, especially on the hemorheology of microcirculation. The aim of this study was to assess the protective function of TXLagainst AS on microcirculation in rats’ mesentery.Materials and Methods: Arteriole spasm model was established by local administration of norepinephrine in rats’ mesentery. Ratswere randomized divided into five groups: sham group (local administration of normal saline), arteriole spasm group, TXL0.4+ASgroup, TXL0.8+AS group, TXL1.6+AS group. Drugs were administered orally daily for 7 days before modeling. Microcirculationwas observed using an upright microscope and recorded to study the hemorheology changes, including spasm time, diameterchanges, and arteriole blood flow. Mast cell degranulation was identified by vital staining with topical application of 0.1% toluidineblue. The serum samples were collected for detect of NO and ET-1.Results: Pre-administration of TXL markedly decreased arteriole spasm time, and indicated a dose-dependent effect.Pre-administration of TXL also indicates dose-dependent effect to maintain arteriole diameter in the presence of AS. Pretreatmentwith TXL significantly inhibited mast cell degranulation induced by AS, TXL also exert great beneficial protection on arterioleblood flow against AS. The serum level of NO and ET-1 had no obvious changes among each groups.Conclusion: AS caused microvascular dysfunction in rats’ mesentery. TXL had a beneficial effect against AS in the perspective ofprotecting microvascular function, indicated that TXL fight against AS through regulation on microcirculation.